Bisphenol A and pubertal height growth in school-aged children - Wang, Ziliang (J Expo Sci Environ Epidemiol, 2018)
BACKGROUND: Bisphenol A (BPA) is an environmental endocrine disruptor and is found in many consumer products. Studies suggest that BPA may perturb pubertal development, although evidence on BPA-influenced pubertal height growth is scarce. METHODS: A total of 754 children aged 9–18 years from three schools (one elementary, one middle, and one high school) in Shanghai were included in this longitudinal study. Height was measured at enrolment (visit 1) and, subsequently, at 19 months after enrolment (visit 2). Age- and sex-specific Z scores for height were calculated (height Z score = [participant’s height−sex- and age-specific population height mean]/sex- and age-specific population height standard deviation). Urine samples were collected at enrolment to measure BPA concentrations. We used multiple linear regression models or general estimating equation models (GEE) to estimate associations between urine BPA level and height Z score. RESULTS: The geometric mean of urine BPA concentrations was 1.6 μg/L (95%CI: 1.4, 1.8) or 1.2 μg/g creatinine (95%CI: 1.0, 1.3). An inverse association between urine BPA level and height was observed in boys. After adjustment for potential confounders, height Z score at enrolment in boys decreased by 0.49 for the highest exposure level (above 10.9 μg/g creatinine as the 90th percentile), compared with the lowest BPA exposure (below 0.2 μg/g creatinine as the 25th percentile) (95%CI: −0.96, −0.01; p-trend = 0.024). The inverse association remained between BPA exposure and height Z score at visit 2. The GEE model showed that a 1-unit increase in log(10)-transformed BPA concentrations was associated with a 0.15-point decrease in height Z score over the follow-up (95%CI: −0.30, −0.01). BPA was not associated with height growth in girls. CONCLUSIONS: Our findings indicate an inverse association between urine BPA level and height growth in boys. These findings need to be confirmed in further studies.